Avaliação do pensamento contrafactual na depressão - Faccioli, Juliana Sarantopoulos (2013)
Counterfactual thinking (CT) corresponds to the idea of mental constructions of alternatives for past event and serves an important function in an individual s adaptation and emotional coping. The aims of this study were to: (1) produce material to access and evaluate the counterfactual thinking of adults and (2) investigate the counterfactual thinking of depressed and non-depressed people, in order to determine if there are differences in how these two groups think about alternatives to reality. Five stories were prepared, using materials extracts from studies of counterfactual thinking, newspaper report and magazines articles. For each story, we formulated questions about thoughts related to the content read and about how these stories might have been different. The alternatives were formulated using aspects of reality most commonly modified by people, according to the literature: action or inaction, obligation, time and unusual events. Judges evaluated the texts and the questions, and ranked the alternatives provided according to aspects of reality that were modified. These materials were then used with 42 adults (85% female, mean age of 43 years). Subjects belonged one of two groups: depressed and non-depressed. Individual interviews were conducted. Initially, participants indicated their reactions to the stories then indicated modifications they would make, and then selected one of a pre-determined list of possible changes. The verbal responses of both groups were categorized using content analysis, and the frequency of responses, for each category, was compared using Student s t-Test. There were similarities in the CT for both groups. The majority of the CT was categorized as upward, subtractive, self-directed and refered to modifications in action or inactions. Few differences between the two groups were observed, mostly found through directed modifications.